Cardiorespiratory coupling in the bottlenose dolphin (Tursiops truncatus) - Fahlman, A.; Mcknight, J. C.; Blawas, A. M.; West, N.; Torrente, A. G.; Aoki, K. (Frontiers in Physiology, 2023)
Introduction: The bottlenose dolphin (Tursiops truncatus) is an intermittent breather, where the breath begins with an exhalation followed by inhalation and an extended inter-breath interval ranging from 10 to 40 s. Breathing has been shown to alter both the instantaneous heart rate (ifH) and stroke volume (iSV) in the bottlenose dolphin, with a transitory ventilatory tachycardia following the breath, and an exponential decrease to a stable ifH around 40 beats • min−1 during the inter-breath period. As the total breath duration in the dolphin is around 1 s, it is not possible to assess the contribution of exhalation and inhalation to these changes in cardiac function during normal breathing. Methods: In the current study, we evaluated the ifH response by separating expiration and inspiration of a breath, which allowed us to distinguish their respective contribution to the changes in ifH. We studied 3 individual male bottlenose dolphins trained to hold their breath between the different respiratory phases (expiration and inhalation). Results: Our data show that inspiration causes an increase in ifH, while expiration appears to result in a decrease in ifH. Discussion: These data provide improved understanding of the cardiorespiratory coupling in dolphins, and show how both exhalation and inhalation alters ifH.